Analysis of Student's Problem Understanding Grade V Elementary School in Solving Mathematical Story Problems - Pani Suswari; Tatang Herman (Jurnal Elementary : Kajian Teori dan Hasil Penelitian Pendidikan Sekolah Dasar, 2020)
The aim of study will to look at skill of student’s problem understanding in solving mathematical story problems. This is study qualitative that describe skill of student’s problem understanding in solving mathematical story problems. The collecting of data is used are test and observation. The analysis of its data are reduction, display, and taking of conclusion. As for resulting of the study seem that skill of student’s problem understanding in solving mathematical story problem was classified moderate, where the means of score as big as 56.34 with the standard of deviation 21,02. Others that, from many students were do the test are looked at that just one of indicator did get answered by more than half of students were doing of test.